Bulk-like behavior in the temperature driven martensitic transformation of Cu-Zn-Al thin films with 2H structure. - Haberkorn, Nestor Fabian (2014)
This paper reports on the possibility to obtain Cu-Zn-Al films with 2H martensitic structure by fixing the valence electron concentration per atom (e/a) ≈1.53. Films with thickness of ≈ 5 um with micrometric grains show martensitic transformation temperature and hysteresis values close to the ones found in bulk samples. This result is different to the one found in Cu-Zn-Al thin films with 18R martensitic structure and similar microstructure, in which the hysteresis presents an increment (≈ 10 times) compared to bulk samples. This difference can be  associated to the intrinsic nature of the 2H transformation which requires more undercooling to produce the nucleation of the martensitic phase. The driving force for the burst-type  martensitic transformation decreases the influence of the microstructure in the transformation.